EFEKTIVITAS MANAJEMEN KEUANGAN PADA SMA NEGERI 1 INDRA JAYA KABUPATEN ACEH JAYA - Muhammad Nasir, Yusrizal, Murniati, Murniati, AR. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
ABSTRACT: Finance in the education sector in schools is essential. Therefore money need to be managed effectively and efficiently in order to help meet the goals of education. The approach used in this study is a qualitative approach with descriptive methods. Data collection techniques used were observation, interview and documentation. Subjects of this study were principal, vice principals, treasurers and teachers. The main purpose of this study was to determine the relevance of financial planning system, the mechanism of financial processes and financial accountability. For the data analysis, this study used descriptive techniques which the implementation was done in three flow of activities, that is, data reduction, data presentation, and conclusion or verification. The results showed that: (1) The relevance of the planning system of school finance plan was agree with the school plan as a whole, both short-term plan and the medium-term. The short-term plans is one-year plan, while the medium-term plan is 4-year plan; (2) Financial planning was focused on the existing budget, that is, School Finance Assistant, and School Budget Planning (RKAS) was compiled based on school strengths in education; (3) The mechanism of financing process was carried out by analyzing the cost per item or per unit of activity, by managing the budget item, that is, the classification of the budget to finance a particular activity. To analyze the cost per item of activity, it needs to create a Budget Plan (RAB) of any activity, so that it finds how much the cost needed by matching the other balanced or no-balanced activities in accordance with the priority scale, and (4) the financial accountability was done by the principal assisted by treasurer, which is reported to government, especially to Regional Education Office.KEYWORDS: effectiveness, management, finance ABSTRAK: Keuangan dalam pendidikan disuatu sekolah merupakan hal yang esensial. Oleh karena itu uang perlu dikelola denga efektif dan efisien agar membantu pencapaian tujuan pendidikan. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode deskritif. Teknik pengumpulan data dengan menggunakan: observasi, wawancara mendalam dan dokumentasi. Subjek penelitian terdiri dari kepala sekolah, wakil kepala sekolah, bendahara dan guru. Tujuan utama penelitian ini adalah: untuk mengetahui relevansi sistem perencanaan keuangan, mekanisme proses keuangan dan pertanggungjawaban keuangan. Analisis data menggunakan teknik deskriptif yang penerapannya dilakukan dalam tiga alur kegiatan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil Penelitian menunjukkan bahwa: (1) Relevansi sistem perencanaan keuangan sekolah disesuaikan dengan rencana sekolah secara keseluruhan, baik rencana jangka pendek maupun jangka menengah. Rencana jangka pendek berupa rencana 1 (satu) tahunan, sedangkan rencana jangka menengah untuk 4 (empat) tahunan pendidikan; (2) Mekanisme proses pembiayan dilakukan dengan cara menganalisis biaya per item atau per unit kegiatan, dengan cara mengatur mata anggaran-mata anggaran, yaitu klasifikasi anggaran untuk membiayai suatu kegiatan tertentu. Menganalisis Kebutuhan biaya per item aktivitas adalah dengan membuat Rencana Anggaran Biaya (RAB) setiap aktivitas sehingga terlihat berapa biaya yang diperlukan dengan mencocokkan dengan aktivitas lain seimbang atau tidak seimbang sesuai skala prioritas dan mendesak dan (3) Pertanggungjawaban keuangan dilakukan oleh kepala sekolah yang dibantu oleh bendahara dalam pembuatan pelaporannya, yang akan dilapor ke pemerintah khususnya Dinas Pendidikan setempatKATA KUNCI: efektivitas, manajemen, keuangan